2015
DOI: 10.4149/neo_2015_101
|View full text |Cite
|
Sign up to set email alerts
|

Pol ζ polymorphisms are associated with platinum based chemotherapy response and side effects among non-small cell lung cancer patients

J Ye1,
et al.

Abstract: Lung cancer is the greatest contributor to tumor-derived death. Traditionally, platinum-based chemotherapies are the primary treatment for most patients. However, intrinsic drug resistance and side effects limit the efficacy of platinum-based chemotherapies. Previous studies demonstrated that Pol ζ can modulate cellular sensitivity to chemotherapy. The primary aim of this study was to investigate the potential role of the polymorphism of Pol ζ in platinum-based chemotherapy tolerance and side effects. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Ye et al . divided patients according to smoking status, genotyped 13 tagSNPs of REV3 and REV7 and found that the five SNPs were correlated with an increased risk of grade 3 or 4 hematologic toxicity …”
Section: Discussionmentioning
confidence: 99%
“…Ye et al . divided patients according to smoking status, genotyped 13 tagSNPs of REV3 and REV7 and found that the five SNPs were correlated with an increased risk of grade 3 or 4 hematologic toxicity …”
Section: Discussionmentioning
confidence: 99%
“…(1) patients diagnosed with NSCLC referred to the diagnostic criteria above; (2) 18-80 years old; (3) patients who were about to undergo the first GP chemotherapy, with an 8-day course of treatment (day 1-3 days and 8); (4) no history of surgery within 6 months before chemotherapy; (5) patients who never participated in any fatigue-related interventions; (6) no infection, injury, and ulcer around the acupoints; (7) patients were diagnosed CRF in line with the CRF diagnostic criteria of the 10th edition of the International Statistical Classification of Diseases and Related Health Problems and were rated as mild and moderate fatigue according to the Chinese version of the Piper Fatigue Scale-Revised (RPFS-CV); (8) had a Karnofsky ðKPSÞ efficacy status score > 60 points, with a predicted survival time > 6 months; (9) no cognitive impairment; and (10) voluntarily participated in this study and provided signed informed consent.…”
Section: Inclusion Criteria the Inclusion Criteria Were As Followsmentioning
confidence: 99%
“…Patients with stages IIb to III lung adenosquamous carcinoma (ASC) are often given platinumbased dual-drug chemotherapy [3] to terminate cancer cell division and inhibit cancer DNA synthesis [4][5][6]. However, these treatments simultaneously damage normal DNA, thereby increasing the risk of gastrointestinal and hematological toxicity [7] and eventually causing fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum compounds induce DNA damage, inhibit DNA replication, and activate a number of signal transduction pathways leading to cancer cell death [ 3 ]. However, these drugs also damage normal cells, leading to severe adverse events [ 4 , 5 ]. Despite initial tumor control, some cancer patients treated with chemotherapies often need to decrease drug doses or stop treatment due to severe adverse events.…”
Section: Introductionmentioning
confidence: 99%